Aprendizagem significativa de monômios: um olhar no contexto da educação bilingue de surdos - Gabe, Neoli Paulina da Silva (2019)
In this research I developed an analysis relating the Meaningful Learning Theory (TAS), with the object of investigation of the pedagogical practices applied in mathe-matics classes, taught in Libras (Brazilian Sign Language), for deaf students. List of the signs of significant learning relating them to the deaf subject, who has his first language (Libras) in visual gestural mode and Portuguese as a second language in written mode. The institution where the research was developed is located in the Rio Pardo Valley region, in the state of Rio Grande do Sul and is a reference in deaf edu-cation. It serves deaf and hearing students, and deaf students in elementary school are attended in special classes with mostly bilingual teachers. In high school they are included in listening classes, with the presence of a Libras / Portuguese language in-terpreter. The objective of this research is to investigate evidence of significant learning in teaching monomials to deaf students. And the problem investigated is: “How is the meaningful learning process of deaf students, users of Libras, in the study of monomi-als?”, A fact that prompted me to constitute this dissertation, seeking to establish an-swers and acquire new knowledge.This research was developed with a class of 8th grade deaf students in special class, relating monomials, polygons and technologies, through the use of Dudamath software. It is concluded that for the meaningful learning process of deaf students, users of Libras, in the study of monomons, the constitution of a concept using the visual, meaning in sign language, is essential. Another factor that led to learning is the use of different methodologies such as geometric figures, software with easy-to-use tools that were proposed during the research and enabled the learning of deaf students with relevant evidence of significant learning, being listed at the end through of concept maps.